Friability and its relationship with clay and organic carbon in soils cultivated with sugar cane (2015)
Friability is a property related to the brittle fracture of soil aggregates and therefore considered as a key to the physical quality of soils and the consumption of energy during farming. This paper contains the preliminary results of research that aimed to quantitatively determine the friability index (FI) and its relationship with other soil properties; in particular, this research focused on the relationship between the FI and the clay content and organic carbon percentage (OC) of soils having a different dominance in the fine fraction (1:1 and 2:1 clay) that were cultivated with sugar cane in the southwest region of Colombia. The FI was determined by the compressive strength method using aggregates with diameters between 9.5mm and 19 mm taken from the surface horizon, which were air air-dried and then dried at a low-temperature in the oven. The type clay content and OC content were determined in these samples. 98.6% of the studied samples, had FI values between 0.24 and 0.80, thus, classifying them as friable (especially those having a 1:1 type clay dominance) and very friable (especially those having a 2:1 type clay dominance), suggesting a structural condition of low to moderate energy requirements for farming, low greenhouse gas emissions (GHG) and a reduced risk of damage on the physical quality if a suitable soil moisture content exists during the tilling. This study found correlations between the texture, OC, and FI of the soils, indicating that the two first properties affected the friability. However, this effect depended on the clay dominance type.